2016
DOI: 10.1038/nn.4352
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of 2,104 trios provides support for 10 new genes for intellectual disability

Abstract: To identify candidate genes for intellectual disability, we performed a meta-analysis on 2,637 de novo mutations, identified from the exomes of 2,104 patient-parent trios. Statistical analyses identified 10 new candidate ID genes: DLG4, PPM1D, RAC1, SMAD6, SON, SOX5, SYNCRIP, TCF20, TLK2 and TRIP12. In addition, we show that these genes are intolerant to nonsynonymous variation and that mutations in these genes are associated with specific clinical ID phenotypes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
415
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 414 publications
(444 citation statements)
references
References 20 publications
16
415
1
1
Order By: Relevance
“…Sleep disturbance affects individuals 1 and 2. We searched previously published datasets of largescale sequencing studies on the causes of neurodevelopmental disability for other reports of de novo KCNQ5 mutations and found c.867G>T (p.Lys289Asn), c.1328G>A (p.Arg443Gln), and c.1727A>G (p.His576Arg) in the supplemental data from 820 probands in Lelieveld et al 17 However, these variants were not identified as candidate causes of neurodevelopmental disability in the course of the authors' statistical analyses. The largest currently published cohort of individuals with developmental disorders (the Deciphering Developmental Disorders study, n ¼ 4,293) did not feature any KCNQ5 de novo variants, 18 nor were any included in the data from the cohort of 2,508 autism probands from Iossifov et al 19 Because of the above evidence associating KCNQ5 mutations with neurodevelopmental disorders, as well as prior evidence that mutations in KCNQ2 (encoding Kv7.2) and KCNQ3 (encoding Kv7.3) most likely cause neurological disease via reduced basal M-current (and subsequent neuronal hyperexcitability), 20 the impact of each mutation was characterized in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Sleep disturbance affects individuals 1 and 2. We searched previously published datasets of largescale sequencing studies on the causes of neurodevelopmental disability for other reports of de novo KCNQ5 mutations and found c.867G>T (p.Lys289Asn), c.1328G>A (p.Arg443Gln), and c.1727A>G (p.His576Arg) in the supplemental data from 820 probands in Lelieveld et al 17 However, these variants were not identified as candidate causes of neurodevelopmental disability in the course of the authors' statistical analyses. The largest currently published cohort of individuals with developmental disorders (the Deciphering Developmental Disorders study, n ¼ 4,293) did not feature any KCNQ5 de novo variants, 18 nor were any included in the data from the cohort of 2,508 autism probands from Iossifov et al 19 Because of the above evidence associating KCNQ5 mutations with neurodevelopmental disorders, as well as prior evidence that mutations in KCNQ2 (encoding Kv7.2) and KCNQ3 (encoding Kv7.3) most likely cause neurological disease via reduced basal M-current (and subsequent neuronal hyperexcitability), 20 the impact of each mutation was characterized in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we added 1,183 de novo variants identified in the exomes of an in-house ID cohort that was previously published. 8 To further reduce the risk of including sequencing artifacts and/or genotyping errors, we excluded all de novo variants that were present more than once in the ExAC dataset (Table S1). 15 These efforts resulted in 6,495 protein coding DNMs, including 4,061 missense mutations, in 5,302 individuals with ID/DD (Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Similarly, largescale WES studies of individuals affected by ID/DD have recently leveraged this phenomenon as supporting evidence of the involvement of a gene in disease. 7,8 This spatial clustering of de novo mutations (DNMs) is typical for missense mutations in genes without clear, or limited numbers of, truncating mutations subsequently degraded by nonsense-mediated mRNA decay, suggesting that these clustered mutations act through a different mechanism than haploinsufficiency (HI). 9 Alternative pathophysiological mechanisms that might underlie (de novo) mutation clustering are gain-of-function or dominant-negative effects, resulting in the alteration or impairment of specific protein function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Recently, large-scale next generation sequencing studies have led to the identification of several DD-associated genes that lead to clinical manifestations through protein truncating or recurrent missense variants. [4][5][6] However, rare disorders caused by private, non-recurrent missense mutations that result in varying phenotypes remain challenging to dissect. 7 Several human DDs are known to result from mutations in members of the RAS superfamily of small GTPases.…”
mentioning
confidence: 99%